Defending against Packet Injection Attacks in Unreliable Ad Hoc Networks - GU, Qijun (Institutional Knowledge at Singapore Management University, 2005)
Ad hoc networks are usually unreliable and have limited bandwidth resources. In such networks, packet injection attacks can cause serious denial-of-service via wireless channel contention and network congestion. To defend against this type of injection attacks, we propose SAF, an efficient and effective Source Authentication Forwarding protocol. The protocol can either immediately filter out injected junk packets with very high probability or expose the true identity of an injector. Differing from other forwarding defenses, this protocol is designed to fit in the unreliable environment of ad hoc networks. Our simulation shows that SAF incurs very lightweight overhead in communication and computation.